Efficacy and safety of L-ornithine L-aspartate combined with lactulose in treatment of hepatic encephalopathy: a systematic review and meta-analysis of randomized controlled trial - Hui Zhang; Yujuan Fu; Minghao Lin; Zheng Nan; Zheng Nan; Dexi Zhao; Dexi Zhao (Frontiers in Medicine)
BackgroundHepatic encephalopathy (HE) represents a collection of metabolic disturbances and regulatory imbalances within the central nervous system that result from advanced liver conditions.PurposeThis article explores the efficacy and safety evaluation of L-ornithine L-aspartate (LOLA) combined with lactulose in the treatment of hepatic encephalopathy based on meta-analysis, providing a rational reference for clinical medication use.MethodsFollowing the PICOS principle, we searched for literature on the treatment of hepatic encephalopathy with Ornithine aspartate combined with lactulose. The literature search was conducted up to and including September 21, 2024. For studies that met the criteria, the Review Manager 5.4 software was used to perform a meta-analysis.ResultsA total of 12 articles were ultimately included, involving 858 patients, with 433 in the treatment group and 425 in the control group. Meta-analysis results: In terms of the total effective rate (RR: 1.31, 95%CI: 1.22, 1.42), the result is statistically significant (Z = 7.15, P = 0.00001 < 0.05), and for AST, ALT, NH3, TBIL, P = 0.00001 < 0.05. The pooled (RR: 1.31 [95% CI = 1.22, 1.42]), which is statistically significant, LOLA and Lactulose is 31% more effective than Lactulose alone in the control group in treating HE.ConclusionThis study indicates that the combination of LOLA and lactulose in the treatment of hepatic encephalopathy has a higher total effective rate in clinical practice and can significantly reduce the levels of AST, ALT, TBIL, and NH3.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024592957.